Systemic Immune Inflammation-Index and CANLPH Score in Patients with Mitral Stenosis Undergoing Balloon Valvuloplasty - Abacioglu, Ozge Ozcan; Yıldırım, Arafat; Karadeniz, Mine; Acele, Armagan; Dindas, Ferhat; Koyunsever, Nemin Yıldız; Dogdus, Mustafa; Kurt, İbrahim Halil (European Journal of Therapeutics, 2023)
Objective: to evaluate CANLPH score and systemic immune inflammation index (SII) in patients with symptomatic rheumatic mitral stenosis (MS) undergoing percutaneous mitral balloon valvuloplasty (PMBV). Methods: 62 patients who underwent PMBV in our clinic between 2018 and 2021 were included retrospectively. The patients were divided into 2 groups according to echo score. The CANLPH score was calculated from the cut-off values of C-reactive protein to albumin ratio (CAR), neutrophil to lymphocyte ratio (NLR) and platelet to hemoglobin ratio (PHR), determined with the Youden index and SII by the formula platelet x neutrophil/lymphocyte. P <0.05 was considered statistically significant. Results: The mean age of the patients was 44.5±10.4 years (40 female, 64.5%). The mean values of SII and CANLPH scores were higher in the Echo score >8 group (p <0.001, both). The mean mitral gradient before and after PMBV was 12.6±5.7mm Hg and 5.0±2.4 mm Hg, and the mean valve area was 1.12±0.27 cm2 and 1.85±0.29 cm2. A statistically significant and negative correlation was observed between the gradient decrease after the procedure and the CANLPH score and SII (r=-0.426, p=0.001 and r=-0.418, p=0.001, respectively). In receiver operating characteristic (ROC) curve analysis, it was concluded that the ability of CANPLH score to predict the higher Echo scores was noninferior to SII with an area under curve (AUC:0.820 (0.701-0.906) and AUC:0.786 (0.664-0.880), z statistics 0.576 and p=0.564. Conclusion: SII and CANLPH scores are correlated with Echo score. A significant negative relationship was found with both biomarkers and gradient decrease after the PMBV.